DEVELOPMENT AND VALIDATION OF A STABILITY INDICATING RPHPLC METHOD FOR SIMULTANEOUS QUANTIFICATION OF LOBEGLITAZONE AND METFORMIN IN TABLET DOSAGE FORMS (International Journal of Food and Nutritional Sciences, 2022)
A stability-indicating RP-HPLC method is proposed for the rapid, sensitive, and selective determination of Lobeglitazone and Metformin in pharmaceutical formulations. Lobeglitazone and Metformin were separated on a Cosmosphere C18 column (250×4.6 mm, 5 µm) using a mobile phase comprising methanol, acetonitrile, and potassium dihydrogen phosphate buffer adjusted to pH 2.5 with orthophosphoric acid (70:5:25 %v/v/v). The gradient elution was optimized at a flow rate of 0.8 mL/min and detection wavelength of 250 nm. Results: The complete method validation was conducted according to ICH guidelines. The recovery study yielded results between 98% and 102% over a concentration range of 50% to 150% of the working concentration. The method demonstrated linearity within the range of 0.5-0.25 µg/mL for Lobeglitazone and 50-250 µg/mL for Metformin, with a linear regression curve (R² = 0.999). The limits of detection (LOD) and quantitation (LOQ) were found to be 0.0010 and 0.0031 µg/mL for Lobeglitazone, and 0.30 and 0.91 µg/mL for Metformin, respectively. The retention times were 8.37 min for Lobeglitazone and 2.83 min for Metformin. The method exhibited good recoveries, and intra-day and inter-day relative standard deviations were below 2%. Ruggedness and robustness were evaluated and found satisfactory as per ICH guidelines. Stability studies under various stress conditions (acid, base, oxidation, thermal, and sunlight) were conducted as recommended by ICH guidelines. Conclusion: The developed RP-HPLC method is suitable for the accurate estimation of Lobeglitazone and Metformin in pharmaceutical formulations. The high recovery rates and low relative standard deviations validate the suitability of the proposed method for routine analysis in bulk and pharmaceutical formulations.